Strengthening separation of powers between the legislature and the executive in Malaysia /Mark Goh Wah Seng - Mark Goh, Wah Seng (2004)
As a constitutional doctrine separation of power was primarily created to prevent for government to prevent from abusing its powers and from acting in arbitrary manners.